Long-term Outcomes of Sphincter-Saving Procedures for Diffuse Crohn's Disease of the Large Bowel. Issue 12 (December 2016) - Li, Yi; Stocchi, Luca; Mu, Xing; Cherla, Deepa; Remzi, Feza H.
Abstract : BACKGROUND: Total abdominal colectomy with ileorectal anastomosis for Crohn's colitis is acceptable in the presence of a suitable rectum. Intentional IPAA has been proposed for diffuse Crohn's proctocolitis without enteric or anoperineal disease. OBJECTIVE: The aim of this study was to evaluate the long-term outcomes of sphincter-saving procedures for large-bowel Crohn's disease. DESIGN: Patients with preoperative Crohn's disease diagnosis undergoing intentional IPAA and ileorectal anastomosis were included. SETTINGS: The study was conducted at a tertiary care research center. PATIENTS: Ileorectal anastomosis was performed in 75 patients with Crohn's disease, whereas 32 patients underwent intentional IPAA. MAIN OUTCOME MEASURES: Long-term functional results and permanent stoma requirement of sphincter-saving operations were assessed. Quality of life and postoperative medication use were also compared with a control group of patients undergoing total proctocolectomy and end ileostomy. RESULTS: Patients undergoing ileorectal anastomosis were older and had longer disease duration, higher prevalence of perianal and penetrating disease, and history of small-bowel resection than those receiving IPAA. Indications for surgery, preoperative use of immunomodulators, and postoperative use of biologics were also significantly different. Although functional defecatory outcomes were comparable, reported quality of life 3 years after surgery was significantly better in patients who underwent IPAA than in patients with ileorectal anastomosis. Patients with IPAA were associated with significantly lower cumulative rates of surgical recurrence (HR = 0.28 (95% CI, 0.09–0.84); p = 0.017), indefinite stoma diversion (HR = 0.35 (95% CI, 0.13–0.99); p = 0.039), and proctectomy with end ileostomy (HR = 0.27 (95% CI, 0.07–0.96); p = 0.030) than those with ileorectal anastomosis. LIMITATIONS: The study was limited by its retrospective nature and small sample size. CONCLUSIONS: Contemporary patients selected to have intentional IPAA for Crohn's colitis have disease characteristics very different from those selected to have ileorectal anastomosis. Long-term follow-up confirms intentional IPAA as an acceptable option in selected patients with Crohn's colitis.